Chronic urticaria and hormones: Is there a link?. (23rd March 2016) - Amsler, E.; Augey, F.; Soria, A.; Boccon‐Gibod, I.; Doutre, M.S.; Mathelier‐Fusade, P.; Nicolas, J.F.; Rayson‐Peyron, N.; Gompel, A.
Abstract: Background: While the role of oestrogens in bradykinin angioedema (AE) has been clearly demonstrated, scarce data are available about the role of sex hormones in chronic urticaria (CU). Objectives: To gather information from a population of women with various forms of CU [chronic spontaneous urticaria (CSU), including a subtype of isolated histaminic AE and a classic subtype of association of wheals and AE, and exclusive inducible urticaria (IU)] about the impact of sex hormones and reproductive factors on their symptoms. Methods: This was a cross‐sectional study comprising interviews of 200 women consulting for CU at nine centres throughout France between May and July 2013. The dermatologists filled in an online questionnaire on the impact of reproductive factors (puberty, contraception and pregnancy) and hormonal treatments on the course of CU, including CSU and IU, in the presence of the women. Results: Most of the women did not experience CU before puberty and if so, puberty did not influence the course of CU. Only 16 women had experienced a pregnancy during CU which caused a worsening of symptoms in four. Hormonal contraception was associated with aggravation in a minority of women, mostly women with CSU (10%). Women with isolated histaminic AE did not exhibit any female sex hormone dependency. Conclusions: It would appear that sex hormones act as a trigger in only a small subset of women with CU. Nevertheless, this should be taken into account to improve patient management.